PEMBERDAYAAN MASYARAKAT DESA DALAM PENINGKATAN KAPASITAS KELEMBAGAAN MASYARAKAT DESA PEMATANG KABAU KECAMATAN AIR HITAM KABUPATEN SAROLANGUN - Is, Asnawati; Fikriman, Fikriman; Setiono, Setiono; Febrialdi, Akhyarnis; Sopandi, Acep (Bersama : Jurnal Pengabdian Kepada Masyarakat, 2024)
Empowering village communities in improving and strengthening community institutional capacity is a community service activity carried out in Pematang Kabau Village, Air Hitam District, Sarolangun Regency. This service activity aims to increase the institutional capacity of the community with existing problems where the quality of the village LPM apparatus resources is not yet optimal and the lack of institutional capacity of the village community in meeting community needs. The method used in this service activity is direct training and mentoring. The result of service activities is an increased understanding of LPM's capacity to help improve community welfare. Each participant has participated in a whole series of activities that can be applied directly to the community by carrying out the stages of empowerment